2019
DOI: 10.1002/slct.201803947
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ni/NiF2‐AlF3 Catalyst with Mild‐Strength Lewis Acid Sites for Dehydrofluorination of 1, 1, 1, 2‐Tetrafluoroethane to Synthesize Trifluoroethylene

Abstract: A novel Ni/NiF2‐AlF3 catalyst was prepared by impregnation and following vapor hydrofluorination, and it was used to dehydrofluorination of tetrafluoroethane to trifluoroethylene. BET, SEM, XRD, XPS, NH3‐TPD and Py‐IR techniques were employed to characterize the Ni/NiF2‐AlF3 catalysts. Based on the NH3‐TPD results, it was interestingly found that the strong acidic sites of Ni/NiF2‐AlF3 catalyst transformed into the mid‐strength acidic sites with the increase of Ni loading, attributing to the roles of Ni on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is well accepted that dehydrochlorination (DeHCl) and dehydrofluorination (DeHF) are catalyzed by Lewis acidic sites over the surface of catalysts. , Due to the stability in HF and HCl corrosive atmospheres, fluorides such as AlF 3 , fluorinated Cr 2 O 3 , and MgF 2 are usually adopted as the catalysts in the fluorine chemical industry. It was suggested that unsaturated coordination sites of Al and Mg are responsible for the strong Lewis acid. , However, there are very few works concerning the relationship between the formation of acidic sites and coordination of metals.…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that dehydrochlorination (DeHCl) and dehydrofluorination (DeHF) are catalyzed by Lewis acidic sites over the surface of catalysts. , Due to the stability in HF and HCl corrosive atmospheres, fluorides such as AlF 3 , fluorinated Cr 2 O 3 , and MgF 2 are usually adopted as the catalysts in the fluorine chemical industry. It was suggested that unsaturated coordination sites of Al and Mg are responsible for the strong Lewis acid. , However, there are very few works concerning the relationship between the formation of acidic sites and coordination of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 and Table S1 exhibited the qualitative and quantitive results, respectively. In Figure 4, the peak at the position of 1442 or 1450 cm −1 corresponded to Lewis acidity and the peak at the position of 1546 cm −1 corresponded to Brönsted acidity [21] . And these two peaks were used to calculate the acid amounts as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4, the peak at the position of 1442 or 1450 cm À 1 corresponded to Lewis acidity and the peak at the position of 1546 cm À 1 corresponded to Brönsted acidity. [21] And these two peaks were used to calculate the acid amounts as shown in Table S1. Al 2 O 3 presented a high amount of Lewis acidity, without any Brönsted acidity.…”
Section: Catalyst Characterizationsmentioning
confidence: 99%
“…It was reported that the catalytic behaviors, especially dehydrofluorination of hydrofluorocarbons, [35,36] was closely related to the catalyst properties such as acidity, [37,38] because the cleavage of C−F bonds as the key of dehydrofluorination could be activated by the acid sites. According to the Table 3, the conversion of ZnO/Cr 2 O 3 catalysts with different surface areas had little difference (∼99 %), suggesting that the surface areas had no effect on the activity of ZnO/Cr 2 O 3 catalysts.…”
Section: Resultsmentioning
confidence: 99%